PRETERM LABOR CONDITIONS OF WOMEN WITH HIGH-RISK PREGNANCY AND RELATED FACTORS: A RETROSPECTIVE COHORT STUDY - Seher Palanbek Yavaş; Caner Baysan (İstanbul Tıp Fakültesi Dergisi)
Objective: High-risk pregnancy is a situation associated with pregnancy involving a real or potential risk for the health and well-being of the mother and the fetus. Our study aimed to examine the preterm labor conditions of pregnant women followed up at a high-risk pregnancy outpatient clinic and related factors. Material and Methods: Designed as a retrospective cohort study, the study was carried out with the participation of 293 pregnant women who presented to a high-risk pregnancy outpatient clinic in the Batman province of Turkey and were followed up between March 2017 and January 2019. Results: The top three high-risk conditions determined in the pregnant women were pregnancy over the age of 35 (n=83, 28.3%), pregnancy in a shorter interval than two years (n=71, 24.2%) and consanguineous marriage (n=60, 20.5%), respectively. Twentypoint-one percent (n=59) of the pregnant women had preterm labor. It was determined that the rates of caesarean section births and births at a private hospital among the pregnant women who had preterm labor were significantly higher in comparison to the pregnant women who gave birth at term (p=0.001, p=0.037, respectively). It was determined that the risk of preterm labor increased OR=5.6 (1.2-25.6) times in the pregnant women with anemia, OR=12.5 (1.3-122.7) times in those with intrauterine fertilization and OR=32.6 (3.2-332.5) times in those with multiple pregnancies. Conclusion: Anemia, multiple pregnancy and intrauterine fertilization increase the risk of preterm labor. Quality prenatal care services are important in terms of protecting the health of the mother and the newborn.